1997
DOI: 10.1128/aac.41.2.427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some excitatory amino acid antagonists and drugs enhancing gamma-aminobutyric acid neurotransmission on pefloxacin-induced seizures in DBA/2 mice

Abstract: The behavioral and convulsant effects of pefloxacin (PEFLO), a quinolone derivative, were studied after intraperitoneal (i.p.) administration to Dilute Brown Agouti DBA/2J (DBA/2) mice, a strain genetically susceptible to sound-induced seizures. The anticonvulsant effects of some excitatory amino acid (EAA) antagonists acting at N-methyl-D-aspartate (NMDA) or alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and kainate (KA) receptors and of some compounds enhancing gamma-aminobutyric acid (GABA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Discrepancies between in vitro and in vivo data may have several origins. One possible explanation is that GABA A is not solely responsible for the convulsant activities of FQs but that other mediators such as glutamate and adenosine may also be involved (11,12,31). It is also possible that the relative contribution of each type of mediator is not the same for all FQs, which possibly explains the differences observed in the types of seizures.…”
Section: Results Of In Vitro Binding Experiments Demonstrated Thatmentioning
confidence: 99%
“…Discrepancies between in vitro and in vivo data may have several origins. One possible explanation is that GABA A is not solely responsible for the convulsant activities of FQs but that other mediators such as glutamate and adenosine may also be involved (11,12,31). It is also possible that the relative contribution of each type of mediator is not the same for all FQs, which possibly explains the differences observed in the types of seizures.…”
Section: Results Of In Vitro Binding Experiments Demonstrated Thatmentioning
confidence: 99%
“…Additionally, fluoroquinolones are moderately lipophilic allowing them to readily penetrate the blood brain barrier and exert neurotoxic effects ( Nau et al., 2010 ). Alternatively, fluoroquinolones may directly activate NMDA receptors, as one animal study found that blocking NMDA receptors in mice prevented the occurrence of fluoroquinolone-induced neurotoxicity ( De Sarro et al., 1997 ). Metronidazole-induced neurotoxicity is also thought to be caused by its inhibitory effect on the GABA receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Convulsion-inducing activity was evaluated according to the procedure of Haley and McCormick [26,27] using four-weekold male ICR mice (25−30 g body weight, n = 6−10). Briefly, an aliquot (10 µl) of a testing sample solution, which was prepared by dissolution in 0.1 mol/l NaOH followed by dilution with saline, was injected into the brain using a Hamilton microsyringe No.…”
Section: Convulsion-induction Test In Micementioning
confidence: 99%